2016
DOI: 10.1155/2016/8682494
|View full text |Cite
|
Sign up to set email alerts
|

Lower Viral Response to Pegylated Interferon Alpha 2a Treatment of Chronic Hepatitis B in Roma People in Eastern Slovakia

Abstract: Aim. To evaluate the compliance and virological response to pegylated interferon alpha 2a treatment of chronic hepatitis B in Roma population compared to majority Caucasian population in Slovakia. Methods. Retrospective evaluation of a cohort of all Roma patients treated with pegylated interferon alpha 2a from 2007 to 2013 in 3 centers for treatment of chronic viral hepatitis B. The Study included 43 Roma patients with chronic viral hepatitis B and randomly selected control group. Treatment duration was 48 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Currently, a multitude of therapeutic options exist for the treatment of chronic hepatitis B, in which patients achieve the virologic response desired in the vast majority of cases. However, Roma have less compliance to the treatment of chronic hepatitis B with pegylated interferons than the majority population [54]. The optimal way to prevent the spread of hepatitis B virus in the Roma settlements would be to vaccinate patients who do not yet show serological markers of hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a multitude of therapeutic options exist for the treatment of chronic hepatitis B, in which patients achieve the virologic response desired in the vast majority of cases. However, Roma have less compliance to the treatment of chronic hepatitis B with pegylated interferons than the majority population [54]. The optimal way to prevent the spread of hepatitis B virus in the Roma settlements would be to vaccinate patients who do not yet show serological markers of hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously published retrospective analysis from our group we reported that Pegylated interferon alpha treatment was completed by 100% patients from the non-Roma but only 79% patients from Roma population ( p = 0.0009). This led to the lower rate of virological response at the end of treatment in Roma population (51% versus 81%; p = 0.003) [ 28 ]. HBsAg positive participants in this study, who fulfilled treatment criteria, were contacted through their general practitioner and were offered the standard of care treatment with nucleot(s)ide analogues or pegylated interferon alpha.…”
Section: Discussionmentioning
confidence: 99%
“…Today, there are two treatment options for chronic hepatitis B-treatment with nucleot(s)ides analogues or PEG IFN alpha 2a [28]. Roma people compliance in the treatment with PEG IFN alpha 2a is suboptimal, which is associated with achieving a poorer virologic response [29]. At present, a long-term treatment with nucleot(s)ides analogues (entecavir, tenofovir, tenofovir alafenamide), which leads to suppression of HBV infection in near to all infected patients is preferred [28].…”
Section: Discussionmentioning
confidence: 99%